The value-for-money assessment and funding arrangements for high-priced drugs in an era of uncertainty: a comparative analysis of national health technology assessment agencies in South Korea, England, Australia, and Canada - Jihyung Hong; Eun-Young Bae; Sohee Cha; Joohyun Lee (BMC Health Services Research)
Abstract Background Innovative health technologies have increasingly emerged as a promising solution for patients with untreatable or challenging conditions. However, these technologies often come with expensive costs and limited evidence at the time of launch. This study assessed how these high-priced drugs with limited evidence were appraised and introduced in South Korea, England, Australia, and Canada, where cost-effectiveness analysis (CEA) generally plays a central role in pricing and reimbursement decisions. Methods The study analysed 22 high-priced drugs (24 indications) introduced in South Korea, which were granted CEA waivers due to difficulties in evidence generation and high unmet needs. Data, including funding arrangements and evidence assessed, were derived from national health technology assessment (HTA) documents and other public domains in the four countries. Results Nearly all drugs received positive recommendations, largely through managed entry agreements (MEAs), particularly in England. Single-arm trials were more common in South Korea and England. Indirect comparison was the primary source of comparative effectiveness in England (70.0%), emphasising alignment with current practices. Australia and Canada utilised both indirect comparison and head-to-head trial data in similar proportions. Except for South Korea, all countries still required CEA data for these drugs. Data collection for coverage with evidence development was necessary in 55.0% of cases in England, and less in other countries. Conclusion HTA agencies increasingly accept the uncertainty of high-priced drugs with high unmet needs through MEAs. To ensure timely access and value for money, implementing full value assessment and uncertainty management, while strengthening national and international collaboration for effective data collection, is imperative.